Anti-Osteoarthritis Mechanism of the Nrf2 Signaling Pathway - Sarmistha Saha; Nazih Y. Rebouh (Biomedicines, 2023)
Osteoarthritis (OA) is a chronic degenerative disease and the primary pathogenic consequence of OA is inflammation, which can affect a variety of tissues including the synovial membrane, articular cartilage, and subchondral bone. The development of the intra-articular microenvironment can be significantly influenced by the shift of synovial macrophages between pro-inflammatory and anti-inflammatory phenotypes. By regulating macrophage inflammatory responses, the NF-κB signaling route is essential in the therapy of OA; whereas, the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway appears to manage the relationship between oxidative stress and inflammation. Additionally, it has been demonstrated that under oxidative stress and inflammation, there is a significant interaction between transcriptional pathways involving Nrf2 and NF-κB. Studying how Nrf2 signaling affects inflammation and cellular metabolism may help us understand how to treat OA by reprogramming macrophage behavior because Nrf2 signaling is thought to affect cellular metabolism. The candidates for treating OA by promoting an anti-inflammatory mechanism by activating Nrf2 are also reviewed in this paper.